Measuring Indonesian EFL Learners’ Beliefs about English Language Learning: A Stochastic Modeling Approach - Dairabi Kamil (Universitas Jambi, Indonesia, 2022)
This research sought to assess the validity and reliability of the Indonesian translation of the Beliefs About Language Learning Inventory (BALLI) and using it to measure Indonesian English as a Foreign Language (EFL) learners’ Beliefs About Language Learning (BALL). Data were collected by administering BALLI to 58 conveniently sampled English department students at a state higher education institution in Indonesia. Data analyses were conducted within a stochastic modeling approach using the Rasch analysis method. The results show that the inventory meets the psychometric property criteria of a valid and reliable instrument for a meaningful measurement of BALL within a stochastic modeling approach. The majority of the participants believed that everyone can learn to speak English, some languages are easier than others, the most important part of learning English is learning new words, it is important to practice a lot, and they wanted to learn to speak English well.